PEDAGOGICAL BASES OF DEVELOPING CREATIVE ACTIVITY OF REQUIREMENTS IN ENGLISH TEACHING - Kamolova Mamlakat Adxamovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation. This article discusses the issues of developing students' creative activity in teaching English. The article also lists the lesson plan, its structure, and the main problems in teaching English.